Integrating Neuroscience Principles into Islamic Religious Education in Elementary Schools - Muhamad Dani Suherman; Usep Suherman (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2025)
Islamic religious education in schools often faces challenges in fostering students’ interest, engagement, and deep comprehension of abstract religious concepts. Responding to this issue, the present study investigates the development and implementation of a neuroscience learning model in Islamic religious education at SDN Wangiwisata Majalaya, Bandung Regency. The main objective was to examine how neuroscience-based approaches can enhance students’ understanding, motivation, and appreciation of religious values while also identifying challenges and opportunities in its application.This research employed a qualitative case study design. Data were collected through classroom observations, in-depth interviews with teachers and students, and documentation analysis of curricula, teaching materials, and evaluation records. The data were analyzed using a descriptive qualitative approach involving reduction, categorization, presentation, and interpretation to uncover recurring themes and patterns related to the integration of neuroscience in learning. The findings demonstrate that the neuroscience learning model has a significant impact on both cognitive and affective domains of learning. About 85% of students reported increased interest in religious lessons, while classroom engagement levels rose by approximately 30%. Furthermore, students’ average final exam scores increased by 25% compared to the previous year, indicating measurable academic improvement. Interviews revealed that students found it easier to relate religious concepts to daily life when taught through neuroscience-based strategies such as visualization, storytelling, and experiential learning. Teachers also acknowledged positive shifts in classroom dynamics, with students showing greater collaboration, confidence, and willingness to apply religious values in practice. However, challenges were identified, including limited teacher knowledge of neuroscience principles, inadequate availability of supporting teaching materials, and the need to align methods with diverse student learning styles. The study concludes that integrating neuroscience principles into Islamic religious education is highly relevant in modern schooling. It provides a scientifically grounded, innovative model that enriches religious instruction, supports deeper value internalization, and creates a more inclusive learning environment. To maximize its potential, professional development programs for teachers and systematic curriculum adjustments are essential.